Health related quality of life (HRQOL)among stroke survivors attending rehabilitation centres in Selangor - Nor Azlin MN,; Rizal AM,; Wei Bi L, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2009)
Background : A cross-sectional survey was carried out in December 2007 to compare the healthrelated quality of life (HRQoL) of stroke survivors with that of general Malaysian population. Methodology : Stroke patients were recruited from two community-based rehabilitation centres in Selangor. HRQoL was assessed using Medical Outcome 36-Item Short-Form Health Survey (SF-36). Result : A total of 61 patients (34 males and 27 females) were interviewed. Majority were Chinese (85%) and a small percentage were Malays (15%). 82% (n=50) were elderly of 60 years and above, and the remaining 18% (n=11) were younger patients. 64% had stroke for one year and more, and 36% were less than a year post-stroke. All subjects were community-dwellers and lived with their families. The result showed that with the exception of bodily pain, the mean score of all SF-36 health domains of stroke patients were lower than that of the general population. The greatest difference was in role physical, followed by physical functioning. Female patients demonstrated higher score than the males in all SF-36 domains, in particular general health (57.2 vs 70.3, p=0.01) and social functioning (52.2 vs 73.1, p=0.00). There were no differences of HRQoL domains after comparison according to poststroke duration (all p>0.05). Conclusion : HRQoL of stroke survivors is lower than that of Malaysian general population in all SF-36 health domains, with the exception of bodily pain.